Accelerating effect of Li2CO3 on formation of monocarbonate and Al-hydroxide in a CA-cement and calcite mix during early hydration. (December 2019) - Manninger, T.; Jansen, D.; Neubauer, J.; Goetz-Neunhoeffer, F.
Abstract: QXRD, calorimetry and pore water analysis were performed, to gain insight into accelerating mechanism of Li2 CO3 on CA-cement with CaCO3 (filler and reactant) and investigate its impact on phase formation. Data were combined with thermodynamic modeling (PhreeqC and GEMS) to gain the equilibrium phase assemblage for comparison. Acceleration was reached by adding 0.05 wt% Li2 CO3 to a CA-CaCO3 mix. Early increase of pH during hydration and higher pH after the main reaction were observed by adding Li2 CO3 . Total heat of hydration after 20 h was higher in the sample without Li2 CO3 . The determined crystalline hydrate content disclosed significant differences. The reference mixture showed 8 wt% CAH10 while there was none in the mixture accelerated by Li2 CO3 . The detected amount of monocarbonate (CO2 -AFm) after 20 h was doubled when accelerated by Li2 CO3 . Formation of a layered double hydroxide, formula [Al2 Li(OH)6 ]2 ·X·nH2 O (with X = ½·CO3 2− or OH − ), acting as catalyst was considered.